Synthesis and characterization of erbium-doped willemite- based glass and glass ceramic from green cullet - Abdul Rashid, Siti Syuhaida (2018)
Over the last few decades, the fabrication of glass ceramics using recycled waste glasses is of growing interest among some researchers to reduce energy consumption and cost of raw materials use. However, most of the previous studies were using only the clear soda lime silica (SLS) glass in the production of the glass ceramics. In this study, green SLS waste glass is used as a source of silica to produce the erbium doped willemite-based glass ceramic (Zn2SiO4:Er3+) using the conventional melt-quenching technique followed by controlled sintering process. The effect of different sintering temperatures (700 to 1100 °C) and dopant compositions (Er2O3= 0, 1, 2, 3, 4, and 5 wt.%) on the physical, structural and optical properties of the glass and glass ceramic samples were investigated using X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), fourier transform infrared (FTIR) spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, and photoluminescence (PL) spectroscopy. Experimental results show that the density and linear shrinkage of the samples increased from 2.35 to 2.86 g/cm3 and 6.17 to 24.56%, respectively, with increasing Er3+ dopant percentage and sintering temperature. The XRD analysis revealed the presence of thermodynamically stable zinc orthosilicate (α-Zn2SiO4) phase at sintering temperatures 800 ºC and above. The morphologies from FESEM image shows an increased in grain size from 65 to 283 nm and the formation of densely packed grains as the sintering temperature increases. The presence of the IR bands corresponding to both SiO4 and ZnO4 tetrahedral from FTIR analysis confirmed the formation of Zn2SiO4 crystal in the sintered samples. From UV-Vis analysis, the optical band gap shows an increment from 3.06 to 3.73 eV as the sintering temperature increased from 800 to 1100 °C which is expected due to the improved crystallinities of the samples. The optical band gap also shows a decrement as the Er3+ composition increased from 3 to 5 wt.%, which might be due to the decrease in compactness of the network and the formation of more non-bridging oxygen (NBO). From PL analysis, the enhancement of the emission intensities of the glass and glass ceramic samples can be observed with the progression of sintering temperature under excitation of 385 nm. The PL analysis also shows that the luminescence intensities are strongly dependent on the improvement in crystallinity and the dopant composition.